CONTRIBUTION OF PHYSICAL THERAPY TO THE REHABILITATION OF PATIENTS WITH AN ISCHAEMIC STROKE - Paul LUCACI; Marius NECULĂEŞ; Danisia HABA (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2018)
This paper aims to highlight the role of physical therapy in the rehabilitation of patients with an ischaemic stroke. The study was conducted on a sample of 7 patients with an ischaemic stroke in the non-dominant hemisphere. The purpose of the paper was to select the most useful physical therapy means for the socio-professional reintegration of patients and for improving their quality of life. Following the medical rehabilitation programs undergone by the subjects, the following were recorded: improvements of their joint mobility, increase in muscle strength, improvement of balance and increase in locomotion capacity.